Формування конфліктологічної культури майбутніх фахівців соціономічної сфери у скандинавських країнах - Браніцька, Тетяна; Branitskay, Tatyana. (My University, 2014)
У статті досліджуються досвід формування конфліктологічної культури майбутніх фахівців соціономіч-ного напряму й особливості викладання конфліктологічних дисциплін в університетах скандинавських країн, зокрема в Норвегії, які можуть бути творчо використані у вітчизняній практиці професійної підготовки майбутніх фахівців соціономічних професій.В основе подготовки и развития конфликтологической культуры специалиста в Норвегии находятся ценностные ориентиры общества, движущегося стремительными темпами к поликультурным, полиэтническим и полилингвистическим сообществам. Они основаны на устояв-шихся ценностях западной демократии: признании прав человека, автономии личности и ее свободы; ответ-ственности; восприятии разнообразия и различия интересов, предпочтений и целей профессиональной деятель-ности человека; активной толерантности и т. д. В статье исследуется опыт формирования конфликтологи-ческой культуры будущих специалистов социономических направлений и особенности преподавания конфлик-тологических дисциплин в университетах скандинавских стран, в частности в Норвегии, что может быть творчески использовано в отечественной практике профессиональной подготовки будущих специалистов со-циономических профессий.At the heart of preparation and development of conflictologic culture of the expert in Norway are valuable reference points of a society which moves fast rates to polycultural, polyethnic and polylinguistic assemblage. They are based on the settled values of the western democracy: a recognition of human rights, autonomies of the person and its freedom; responsibility of perception of a diversity and distinction of interests, preferences and the purposes of professional work of the person. In the article the formation experience conflictologic culture of the future specialists of socioeconomic sphere and features of teaching conflictologic disciplines at the universities of the Scandinavian countries, namely, in Norway that can be creatively used in domestic practice of vocational training of the future specialists socioeconomic trades is investigated.
Formation of Conflictological Culture of Future Specialists of Socioeconomic Sphere in the Scandinavian Countries
Keywords: конфліктологічна культура, соціономічні професії, майбутні фахівці; конфликтологическая культура, социономические профессии, будущие специалисты.; conflictologic culture, socioeconomic trades, the future specialists.